The Green Economy: The Dangerous Path of Nature Commoditization - Wilson, Mark (Consilience, 2013)
UNEP’s proposal of the green economy advocates the pricing of ecosystem services in the hope of providing greater environmental protection. There are five aspects which could undermine its practical implementation as well as its social legitimacy; i) ecosystem services are inherently difficult to price, ii) the consideration of the rebound effect is insufficient, iii) primacy of economics over the environment is ensured, iv) markets offer little protection for the poorest people, and v) existing market mechanisms aimed at safeguarding the environment have not succeeded. The green economy relies upon the discursive power of ecological modernisation and our faith in progress to uphold a failing strategy of unfettered economic growth. This discourse limits our capacity to conceive solutions outside the economic sphere. Achieving sustainable development will require a process of social change tha could be facilitated by the acceptance that nature is more than just a form of capital.